Integrated design by optimization of electrical energy systems - Roboam, Xavier (London : ISTE Ltd., 2012)
"This book presents the vision of French academics about systemic design methodologies applied to electrical energy systems. It is especially dedicated to discussion of analysis and system management, as well as modeling and sizing tools"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Electric power systems -- Design and construction; Electronic books